Adverse effects from selected antidotes commonly used in poisonings. (April 2021) - Hoegberg, Lotte C.G.; Boegevig, Soeren
Abstract : Summary: The number of specific antidotes available is low compared to the wide range of substances, of natural or synthetic origin, able to produce toxic symptoms in the human body. Some of these antidotes being very specific in target and effect, e.g., antagonism at the μ-opioid receptors by naloxone in an opioid overdose, other antidotes being unspecific, e.g., glucagon or atropine in the case of betablocker poisoning or activated charcoal with its ability reduce absorption of a wide range of toxic substances. In the following, we present four important antidotes (N-acetylcysteine, deferoxamine, methylene blue and physostigmine) and focus on some of their reported potentially severe adverse effects.